The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1373/clinchem.2007.100917
|View full text |Cite
|
Sign up to set email alerts
|

Postanalytical External Quality Assessment of Urine Albumin in Primary Health Care: An International Survey

Abstract: BACKGROUND: Microalbuminuria (MA) is recognized as an important risk factor for cardiovascular and renal complications in diabetes. We sought to evaluate how screening for MA is conducted and how urine albumin (UA) results are interpreted in primary care internationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…This activity should be extended and be an integrated part of all EQAS activity (7). Post-analytical schemes have been conducted on a project basis across European countries for different POCT analysis (33)(34)(35). For anticoagulation treatment a post-analytical scheme is established in the Czech Republic (15), and recently a post-analytical survey for INR has been carried out in fourteen European countries (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…This activity should be extended and be an integrated part of all EQAS activity (7). Post-analytical schemes have been conducted on a project basis across European countries for different POCT analysis (33)(34)(35). For anticoagulation treatment a post-analytical scheme is established in the Czech Republic (15), and recently a post-analytical survey for INR has been carried out in fourteen European countries (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…During 2006, a questionnaire-based evaluation of urine albumin assessment in primary healthcare was conducted in 9 European countries, with replies received from 2078 general practitioners (55 ). Spot urine samples prevailed for first-time examination of urine albumin, whereas timed collections were used to a larger extent for a repeat test, especially when carried out in a hospital laboratory.…”
Section: Urine Sample Collection and Testing Practicesmentioning
confidence: 99%
“…The goal of such involvement must be to make them more consistent and more easily understood. The potential for laboratory involvement in the postanalytical application of laboratory tests has been demonstrated in a number of studies, including this report from primary care (11 ).…”
mentioning
confidence: 90%
“…The authors of this study (11 ) concluded that guideline recommendations were not being followed and that there was marked variation in whether to use random or spot, early or first-morning urine samples. Timed samples were used extensively in some countries but not in others, and many physicians did not follow up on a positive test result with a repeat test for confirmation.…”
mentioning
confidence: 98%
See 1 more Smart Citation